A novel interdependence based multilevel thresholding technique using adaptive equilibrium optimizer. (September 2020) - Wunnava, Aneesh; Naik, Manoj Kumar; Panda, Rutuparna; Jena, Bibekananda; Abraham, Ajith
Abstract: The multilevel thresholding is one important operation in computer vision, which is a subfield of artificial intelligence (AI), used to understand and interpret the data in the real world. The existing entropic methods, based on the histogram of an image for the multilevel thresholding mostly deal with the maximization of the entropic information excluding the shred boundary, which reduces the accuracy. These problems lead to the poor thresholding accuracy and a lower speed. To address the problem, we propose a novel interdependence based technique that uses the shred boundary, which is a minimization problem. A firsthand objective function is investigated, which takes care of the shred boundary. The traditional multilevel thresholding techniques are computationally expensive due to the exhaustive search process, an alternate method is to use the evolutionary computation based on a nature-inspired algorithm. In this paper, a new optimizer called adaptive equilibrium optimizer (AEO) is also proposed for multilevel thresholding, an improvement over the basic equilibrium optimizer (EO) by implementing an adaptive decision making of dispersal for nonperformer search agents. The AEO performance is compared with state-of-the-art algorithms — equilibrium optimizer (EO), gray wolf optimizer (GWO), whale optimization algorithm (WOA), squirrel search algorithm (SSA) and the wind driven optimization (WDO) algorithm, using standard benchmark functions. Based on the qualitative and quantitative analysis, the AEO outperformed EO, GWO, WOA, SSA, and WDO. The optimal thresholds are obtained by minimizing the objective function using the AEO. For the experiment, 500 images of the BSDS 500 dataset are considered. Popular metrics such as the peak signal to noise ratio (PSNR), structural similarity index (SSIM), and the feature similarity index (FSIM) are considered for a quantitative analysis. Remarkable differences in the thresholding accuracy are observed with a simultaneously decreasing computational complexity. The merits of the paper are highlighted to ensure its future use in the world of engineering applications using soft computing, a subfield of the AI. Highlights: AI technique for multilevel image thresholding is fostered. The objective function is investigated for interdependency minimization. A new adaptive equilibrium optimizer is proposed and validated. Both quantitative and qualitative analysis using statistical methods is done. Experimental results on BSDS 500 dataset are presented.